Love vs. principle: Fans' dilemma over idols promoting or collaborating with boycotted products - Fitria, Kusnul (Jurnal Komunikasi, 2025)
This study explores the attitudes of K-pop fans when faced with the dilemma of their idols collaborating with boycotted products. The research was conducted qualitatively by combining digital ethnography and audiovisual analysis methods. Data were collected through observations of K-pop fans' activities on TikTok and Twitter (X). The findings reveal that K-pop fans display three main attitudes in response to their idols' collaboration with boycotted products. The first attitude is to continue to be a fan and support the idol. However, this support is expressed through various reasons and actions, such as making donations that reflect conditional loyalty and ambiguous participation. The second attitude is active rejection, carried out through participation in cancel culture. This is expressed by unfollowing the idol's social media accounts and deleting fan pages. The third attitude is leaving the fandom and becoming a haters. Although not all fans who leave the fandom become haters, feelings of disappointment and betrayal by the idol are the main reasons behind this response.